Glycogen Metabolism Impairment via Single Gene Mutation in the glgBXCAP Operon Alters the Survival Rate of Escherichia coli Under Various Environmental Stresses - Wang, Mengmeng; Liu, Qinghua; Kang, Xingxing; Zhu, Zuobin; Yang, Huan; Xi, Xiangyu; Zhang, Xiao; Du, Yan; Guo, Mengzhe; Tang, Daoquan; Wang, Liang (Frontiers in Microbiology, 2020)
Glycogen is a highly branched polysaccharide that is widely present in all life domains. It has been identified in many bacterial species and functions as an important energy storage compound. In addition, it plays important roles in bacterial transmission, pathogenicity, and environmental viability. There are five essential enzymes (coding genes) directly involved in bacterial glycogen metabolism, which forms a single operon glgBXCAP with a suboperonic promoter in glgC gene in Escherichia coli. Currently, there is no comparative study of how the disruptions of the five glycogen metabolism genes influence bacterial phenotypes, such as growth rate, biofilm formation, and environmental survival, etc. In this study, we systematically and comparatively studied five E. coli single-gene mutants (ΔglgC, ΔglgA, ΔglgB, ΔglgP, ΔglgX) in terms of glycogen metabolism and explored their phenotype changes with a focus on environmental stress endurance, such as nutrient deprivation, low temperature, desiccation, and oxidation, etc. Biofilm formation in wild-type and mutant strains was also compared. E. coli wild-type stores the highest glycogen content after around 20-h culture while disruption of degradation genes (glgP, glgX) leads to continuous accumulation of glycogen. However, glycogen primary structure was abnormally changed in ΔglgP and ΔglgX. Meanwhile, increased accumulation of glycogen facilitates the growth of E. coli mutants but reduces glucose consumption in liquid culture and vice versa. Glycogen metabolism disruption also significantly and consistently increases biofilm formation in all the mutants. As for environmental stress endurance, glycogen over-accumulating mutants have enhanced starvation viability and reduced desiccation viability while all mutants showed decreased survival rate at low temperature. No consistent results were found for oxidative stress resistance in terms of glycogen metabolism disruptions, though ΔglgA shows highest resistance toward oxidation with unknown mechanisms. In sum, single gene disruptions in glgBXCAP operon significantly influence bacterial growth and glucose consumption during culture. Accumulation and structure of intracellular glycogen were also significantly altered. In addition, we observed significant changes in E. coli environmental viabilities due to the deletions of certain genes in the operon. Further investigations shall be focused on the molecular mechanisms behind these phenotype changes.